ORGANOLOGI MUSIK SALONG: CERMINAN BUDAYA MASYARAKAT HALONG KABUPATEN BALANGAN - Najamudin, Muhammad; Jafira Liana Melanbiru; Benny Mahendra (Jurnal Penelitian Musik, 2025)
Salong is a traditional musical instrument originating from Halong Village, Balangan Regency. This study aims to describe the organology of the salong instrument in terms of its structure, manufacturing process, and the sound production it generates. The research employs a qualitative approach that produces descriptive data in the form of written or spoken words from individuals and observable behaviors. To support the qualitative approach, this study collects both primary and secondary data focusing on the object and subjects of research. Data collection techniques include observation, interviews, and documentation.The results of this study describe the following: (1) The history of salong, (2) Inventory of salong, (3) Terminology of salong, (4) Classification of salong as an idiophone instrument, (5) Description of salong, (6) Sound production of salong, which consists of six stages: Stage I: Preparation (preparing tools and raw materials) Stage II: Manufacturing process (removing branches, cutting bamboo into five pieces, creating resonator tubes) Stage III: Tuning process of the salong Stage IV: Finishing (assembling bamboo components, smoothing each bamboo blade on the salong) Stage V: Testing phase (assessing the instrument's functionality and quality) Salong represents a living and dynamic cultural heritage, reflecting the character of the Halong community that upholds the values of tradition, togetherness, and the preservation of local cultural heritage.